Singing-Related Neural Activity Distinguishes Four Classes of Putative Striatal Neurons in the Songbird Basal Ganglia - Goldberg, Jesse H. (American Physiological Society, 2010)
The striatum—the primary input nucleus of the basal ganglia—plays a major role in motor control and learning. Four main classes of striatal neuron are thought to be essential for normal striatal function: medium spiny neurons, fast-spiking interneurons, cholinergic tonically active neurons, and low-threshold spiking interneurons. However, the nature of the interaction of these neurons during behavior is poorly understood. The songbird area X is a specialized striato-pallidal basal ganglia nucleus that contains two pallidal cell types as well as the same four cell types found in the mammalian striatum. We recorded 185 single units in Area X of singing juvenile birds and, based on singing-related firing patterns and spike waveforms, find six distinct cell classes—two classes of putative pallidal neuron that exhibited a high spontaneous firing rate (>60 Hz), and four cell classes that exhibited low spontaneous firing rates characteristic of striatal neurons. In this study, we examine in detail the four putative striatal cell classes. Type-1 neurons were the most frequently encountered and exhibited sparse temporally precise singing-related activity. Type-2 neurons were distinguished by their narrow spike waveforms and exhibited brief, high-frequency bursts during singing. Type-3 neurons were tonically active and did not burst, whereas type-4 neurons were inactive outside of singing and during singing generated long high-frequency bursts that could reach firing rates over 1 kHz. Based on comparison to the mammalian literature, we suggest that these four putative striatal cell classes correspond, respectively, to the medium spiny neurons, fast-spiking interneurons, tonically active neurons, and low-threshold spiking interneurons that are known to reside in area X.